Efficacy and safety of sodium cantharidinate and vitamin B6 injection for the treatment of digestive system neoplasms: a meta-analysis of randomized controlled trials - Liu MR; Xu CH; Sun YY (Dove Medical Press, 2018)
Meirong Liu,1 Chunhong Xu,2 Yingying Sun3 1Department of Oncology, Liaocheng People’s Hospital, Liaocheng Clinical School of Taishan Medical University, Liaocheng 252000, Shandong Province, China; 2Department of Gastroenterology, Liaocheng People’s Hospital, Liaocheng Clinical School of Taishan Medical University, Liaocheng 252000, Shandong Province, China; 3Department of Radiotherapy, Liaocheng People’s Hospital, Liaocheng Clinical School of Taishan Medical University, Liaocheng 252000, Shandong Province, China Objective: To systematically evaluate the efficacy and safety of sodium cantharidinate and vitamin B6 (SC/B6) combined with conventional medical treatment (CMT) for the treatment of patients with advanced digestive system neoplasms (DSNs). Methods: The Cochrane Library, Embase, PubMed, Web of Science, Chinese Scientific Journal Database (VIP), China National Knowledge Infrastructure, and Wanfang databases were searched for clinical trials using SC/B6 for DSNs. Outcome measures, including therapeutic efficacy, quality of life (QoL), and adverse events, were extracted and systematically evaluated. Results: Data from 24 trials including 1,825 advanced DSN patients were included. Compared with CMT alone, its combination with SC/B6 significantly improved the patients’ overall response rate (OR =2.25, 95% CI =1.83–2.76, P<0.00001), disease control rate (OR =2.41, 95% CI =1.85–3.15, P<0.00001), and QoL improvement rate (OR =2.75, 95% CI =2.13–3.55, P<0.00001). Moreover, adverse events caused by chemotherapy, including leukopenia, nausea and vomiting, gastrointestinal side effects, hepatotoxicity, diarrhea, transaminase disorder, myelosuppression, anorexia, and anemia, were significantly alleviated (P<0.05) when SC/B6 was applied to DSN patients. Nephrotoxicity, thrombocytopenia, hand-foot syndrome, and oral mucositis were not significantly alleviated in patients receiving combination therapy (P>0.05). Conclusion: The combination of SC/B6 and CMT is more effective in treating DSNs than CMT alone. This combination alleviates the adverse effects associated with chemotherapy and improves the QoL of DSN patients, and its application in the clinic is worth promoting. Keywords: sodium cantharidinate and vitamin B6, conventional medical treatment, digestive system neoplasms, meta-analysis